Animal husbandry and grazing potential in the Sahel: An atlas of Niger - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
One of the chief objectives of CTA is to compile scientific and technical information and prepare state-of-theart studies based on available, though very often scattered, data. The preparation of an atlas of the Sahel region is becoming a necessity...